Evaluation of WHO screening algorithm for the presumptive treatment of asymptomatic rectal gonorrhoea and chlamydia infections in at-risk MSM in Kenya. (10th December 2013) - Sanders, Eduard J; Wahome, Elizabeth; Okuku, Haile Selassie; Thiong'o, Alexander N; Smith, Adrian D; Duncan, Sarah; Mwambi, John; Shafi, Juma; McClelland, R Scott; Graham, Susan M
Abstract : Objectives: The WHO recommends that men who have sex with men (MSM) reporting unprotected receptive anal intercourse (RAI) and either multiple partners or a partner with a sexually transmitted infection (STI) in the past 6 months should be presumptively treated for asymptomatic rectal Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) infections. We evaluated this recommendation in a cohort of 'high-risk' MSM in Coastal Kenya. Methods: We assessed presence of genitourinary and rectal symptoms, and determined prevalence and 3-month incidence of rectal NG and CT infections. We performed nucleic acid amplification testing of urine and rectal swab samples collected from MSM followed prospectively, and assessed predictive values of the WHO algorithm at baseline screening. Results: Of 244 MSM screened, 240 (98.4%) were asymptomatic, and 147 (61.3%) reported any RAI in the past 6 months. Among 85 (35.4%) asymptomatic MSM meeting criteria for the WHO presumptive treatment (PT) recommendation, we identified 20 with rectal infections (six NG, 12 CT and two NG–CT co-infections). Among 62 asymptomatic MSM who did not meet criteria, we identified seven who were infected. The sensitivity and specificity of the WHO algorithm were 74.1% (95% CI 53.7% to 88.9%) and 45.8% (95% CI 36.7% to 55.2%), respectively. The 3-month incidence of any rectal NG or CT infection in asymptomatic men reporting any RAI was 39.7 (95% CI 24.3 to 64.8) per 100 person-years. Conclusions: About one-third of asymptomatic MSM were eligible to receive PT for NG and CT infections. Among MSM who would qualify for PT of rectal STIs, the number needed to treat in order to treat one infection was four. Our results support the value of the WHO screening algorithm and recommended PT strategy in this population.